Micro Expression of Students’ Anxiety in Speaking Performance - Santoso, Amanda Nisa Natasha; Qonaatun, Aa; Hendra, Hendra (English Education, Linguistics, and Literature Journal, 2025)
The research aims to understand micro expression of students’ anxiety in speaking performance. This research takes the title of micro expression of students’ anxiety in speaking performance. Micro Expression is the science of reading expression that appear of students’ anxiety of a second. This research uses a qualitative approach with content analysis method. Data collecting technique in this research are observation, interview, and documentation. This shows that students have different expression and anxiety in their speaking performance, and the writers found three factors that cause students' anxiety when speaking English, which are communication anxiety, test anxiety, and fear of being negatively evaluated, influenced by specific anxiety in each situation. This situation can be an emotionally and physically unpleasant experience for some English-speaking students in the class. Students feel anxious, depressed, scared, nervous, and worried when they cannot speak English. Those make students afraid of making mistakes and like to underestimate their abilities, making them unable to perform verbal activities.